A Novel Phospholipase A2 (D49) from the Venom of the Crotalus oreganus abyssus (North American Grand Canyon Rattlesnake). (24th February 2014) - Martins, W.; Baldasso, P. A.; Honório, K. M.; Maltarollo, V. G.; Ribeiro, R. I. M. A.; Carvalho, B. M. A.; Soares, A. M.; Calderon, L. A.; Stábeli, R. G.; Caballol, M. A. O.; Acosta, G.; Oliveira, E.; et al.
Abstract : Currently, Crotalus viridis was divided into two species: Crotalus viridis and Crotalus oreganus . The current classification divides "the old" Crotalus viridis into two new and independent species: Crotalus viridis (subspecies: viridis and nuntius ) and Crotalus oreganus (subspecies: abyssus, lutosus, concolor, oreganus, helleri, cerberus, and caliginis ). The analysis of a product from cDNA (E6d), derived from the gland of a specie Crotalus viridis viridis, was found to produce an acid phospholipase A2 . In this study we isolated and characterized a PLA2 (D49) from Crotalus oreganus abyssus venom. Our studies show that the PLA2 produced from the cDNA of Crotalus viridis viridis (named E6d) is exactly the same PLA2 primary sequence of amino acids isolated from the venom of Crotalus oreganus abyssus . Thus, the PLA2 from E6d cDNA is actually the same PLA2 presented in the venom of Crotalus oreganus abyssus and does not correspond to the venom from Crotalus viridis viridis . These facts highlight the importance of performing more studies on subspecies of Crotalus oreganus and Crotalus viridis, since the old classification may have led to mixed results or mistaken data.